Raising Keynes A Twenty-First-Century General Theory - Marglin, Stephen A. (Harvard University Press, 2021)
Keynes's General Theory has been misunderstood as relying on frictions to justify the need for the visible hand of government to complement the invisible hand of the market. Fleshing out the GT with tools not available to Keynes, Marglin exposes the fundamental failure of markets to self-regulate and draws lessons for fiscal and monetary policies